Managing soil health for doubling citrus yield - Srivastava, A K (Indian Horticulture, 2019)
The perennial fruit trees play an important role in carbon cycle of terrestrial ecosystems and sequester atmospheric CO2. In citrus trees, carbon sequestration in biomass ranged from 23.9 tonnes CO2/ha for young trees to 109 tonnes CO2/ ha for mature trees. With the availability of more technical know-how on combined use of organic manures, prolonged shelf-life of microbial biofertilizers, and inorganic chemical fertilizers, an understanding on nutrient acquisition and regulating the water relations would help switch orchards to CO2 sink (expanding carbon capturing capacity of rhizosphere) so that a more sustainable fruit-based integrated crop production system under biotic and abiotic stress could be evolved. Citrus is undoubtedly one such potentially very promising fruit crop, while looking for neutralising the increasing menace of climate change-related issues.